Sputtered ion emission under size‐selected Arn+ cluster ion bombardment. (28th February 2012) - Gnaser, Hubert; Ichiki, Kazuya; Matsuo, Jiro
<x xml:space="preserve">Abstract</x> The emission of positive secondary ions from four amino acids (arginine, glycine, phenylalanine, and tyrosine) and from NaCl under irradiation with large Arn+ cluster ions was investigated by time‐of‐flight secondary ion mass spectrometry. Size‐selected 5.5‐keV Arn+ cluster ions with 300 ≤ n ≤ 2000 were used, and the flux of sputtered positive ions was monitored as function of cluster size n. For all cluster sizes, the protonated or the cationized molecular ions are observed in the mass spectra. In addition, the results show that with increasing cluster size, the number of fragment molecules strongly decreases in relation to the intact molecules, to the extent that the ratio of fragment to intact ions is 10% or less for the largest cluster ions. Generally, the ion yields Y+ were found to decrease for decreasing impact energy per cluster atom, E/n, and this attenuation was recorded down to values as low as E/n ~ 3 eV/atom. The general trend of Y+ versus E/n is similar for all targets and appears to follow a power‐law dependence, Y+ ∝ (E/n)x, with x ~ 4. This pronounced yield change could be ascribed to a reduction of the ionization probability which is envisaged to depend on the presence of free protons. Their number is expected to decrease concurrently with the decreasing amount of fragmentation for large cluster ions (i.e. for low energies/atom). Copyright © 2012 John Wiley & Sons, Ltd.